(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The article presents the social, economic and environmental benefits resulting fromthe existence of a branded touristic product in rural areas. An example of the branded tourist product are Hortulus Gardens in Dobrzyca. The article shows marketing activi-ties related to development of product and their influence on the forming of the tourism image of the Central Pomerania.